Interdental plaque reduction after use of different devices in young subjects with intact papilla: A randomized clinical trial. Issue 3 (2nd October 2017) - Graziani, F; Palazzolo, A; Gennai, S; Karapetsa, D; Giuca, MR; Cei, S; Filice, N; Petrini, M; Nisi, M
Abstract: Objectives: To determine the efficacy of 4 different oral hygiene regimens involving adjunctive interdental cleaning devices in unsupervised young subjects with intact interdental papilla. Material and methods: Sixty periodontally healthy subjects were randomly allocated to 4 groups following different oral hygiene regimens (T‐7): use of manual toothbrush alone; manual toothbrush plus dental floss; manual toothbrush plus interdental brushes; and manual toothbrush plus rubber interdental picks. Oral hygiene instructions (OHI) were given. One week after (T0), professional supragingival scaling and polishing was performed, and subjects were then reseen every 2 weeks (T14 and T28). At T‐7, T0, T14 and T28, full‐mouth plaque score (FMPS), full‐mouth bleeding score (FMBS) and angulated bleeding index (AngBI) were taken. Results: During the first week (T‐7/T0 unclean phase), FMPS decreased significantly in all groups except the group using dental floss. At T28, a significant decrease in FMPS ( P  < .001, all groups) and FMBS ( P  < .05, all groups except the group using flossing P  < .001) was noted. Interdental FMPS showed significantly lower values in subjects treated with interdental brushes or rubber interdental picks vs toothbrushing alone ( P  < .05). The use of interdental picks was associated with reduced interdental FMBS when compared to flossing ( P  < .05). Conclusion: In young subjects, with no interdental attachment loss, toothbrushing or toothbrushing and adjunctive interdental cleaning devices such as dental floss, interdental brushes or interdental rubber picks can significantly reduce both plaque and gingival inflammation. Use of interdental brushes or rubber picks reduces more interdental plaque in comparison with toothbrushing alone.